Validated LC-MS/MS Method for Simultaneous Quantitation of SAFit-1 and SAFit-2 in Mice Plasma: Application to a Pharmacokinetic Study - Gabani, Bhavesh Babulal; Sulochana, Suresh Ponnayyan; Siddesh, Anup H.A.; Kiran, Vinay; Saini, Neeraj Kumar; Samanta, Swapan Kumar; Hallur, Mahanandeesha S.; Rajagopal, Sridharan; Mullangi, Ramesh (Drug Research, 2020)
SAFit-1 and SAFit-2 are selective FKBP51 (FK506-binding protein 51) ligands. In this paper, we present the development and validation data of an LC-MS/MS method for the simultaneous quantitation of SAFit-1 and SAFit-2 in mice plasma as per FDA regulatory guideline. SAFit-1 and SAFit-2 along with internal standard were extracted from mice plasma using liquid-liquid extraction method. Chromatographic resolution of SAFit-1, SAFit-2 and the internal standard (warfarin) was achieved on an X-Terra phenyl column using 0.2% formic acid:acetonitrile (20:80, v/v) as an eluent, which was delivered at a flow-rate of 0.9 mL/min. The MS/MS ion transitions monitored were m/z 748.4→420.4, 803.7→384.3 and 309.2 →163.2 for SAFit-1, SAFit-2 and the internal standard, respectively. The linearity range was 2.45–2446 ng/mL for both SAFit-1 and SAFit-2. The intra- and inter-day accuracy and intra- and inter-day precision were in the range of 0.90–1.07 and 2.38–10.8%, respectively for SAFit-1; 0.97–1.15 and 0.23–12.5%, respectively for SAFit-2. Both SAFit-1 and SAFit-2 were found to be stable in stability studies (up to three freeze-thaw cycles and for long-term at −80°C for 30 days) and processed (bench-top for 3 h and in in-injector for 16 h) samples. The application of the validated method was shown in a pharmacokinetic study in mice.
Keywords: antidepressant drugs; drug research; pharmacokinetics